Electrical Conductivity Studies on Co(II), Cu(II),Ni(II) and Cd(II) Complexes of Azines - M. Revanasiddappa; Syed Khasim; S. C. Raghavendra; C. Basavaraja; T. Suresh; S. D. Angadi (E-Journal of Chemistry)
1-Phenyl-4-(2'-hydroxyphenyl-1-yl)di-imino azine, {1P-4-(2' HPDA)} 1, 4(2'-hydroxyphenyl-1-yl)di-imino azine, {1, 4-(2' HPDA)} are derived from benzophenone hydrozone with different aldehydes in presence of few drops of concentrated hydrochloric acid in alcoholic medium. Metal(II) complexes have been prepared by salts of CoCl2, CuCl2, NiCl2 and CdCl2 reacting with azine ligands dissolved in alcohol in the molar ratio of (1:2). The prepared complexes were characterized by using various physical methods viz. elemental, molar conductance, magnetic susceptibility, IR, NMR, XRD and UV-Visible. Conductivity of the powder samples were measured by two probe method. Measured electrical conductivities of Co(II), Cu(II), Ni(II) and Cd(II) complexes of azines are reported in this paper. It is found that at room temperature these complexes show insulator behavior. At higher temperature conductivity increases linearly, showing semi conducting behavior.